Axonal Non-segregation of the Vesicular Glutamate Transporter VGLUT3 Within Serotonergic Projections in the Mouse Forebrain - Belmer, Arnauld; Beecher, Kate; Jacques, Angela; Patkar, Omkar L.; Sicherre, Florian; Bartlett, Selena E. (Frontiers in Cellular Neuroscience, 2019)
A subpopulation of raphe 5-HT neurons expresses the vesicular glutamate transporter VGLUT3 with the co-release of glutamate and serotonin proposed to play a pivotal role in encoding reward- and anxiety-related behaviors. Serotonin axons are identifiable by immunolabelling of either serotonin (5-HT) or the plasma membrane 5-HT transporter (SERT), with SERT labeling demonstrated to be only partially overlapping with 5-HT staining. Studies investigating the colocalization or segregation of VGLUT3 within SERT or 5-HT immunolabeled boutons have led to inconsistent results. Therefore, we combined immunohistochemistry, high resolution confocal imaging and 3D-reconstruction techniques to map and quantify the distribution of VGLUT3 immunoreactive boutons within 5-HT vs SERT- positive axons in various regions of the mouse forebrain, including the prefrontal cortex, nucleus accumbens core and shell, bed nucleus of the stria terminalis, dorsal striatum, lateral septum, basolateral and central amygdala and hippocampus. Our results demonstrate that about 90% of 5-HT boutons are colocalized with SERT in almost all the brain regions studied, which therefore reveals that VGLUT3 and SERT do not segregate. However, in the posterior part of the NAC shell, we confirmed the presence of a subtype of 5-HT immunoreactive axons that lack the SERT. Interestingly, about 90% of the 5-HT/VGLUT3 boutons were labelled for the SERT in this region, suggesting that VGLUT3 is preferentially located in SERT immunoreactive 5-HT boutons. This work demonstrate that VGLUT3 and SERT cannot be used as specific markers to classify the different subtypes of 5-HT axons.